The Incidence, Clinical Features, and a Comparison Between Early and Delayed Onset of Postoperative Spinal Epidural Hematoma. Issue 6 (15th March 2019) - Anno, Masato; Yamazaki, Takashi; Hara, Nobuhiro; Ito, Yusuke
Abstract : Study Design: A retrospective observational study. Objective: To investigate the incidence and clinical features of symptomatic postoperative spinal epidural hematoma (PSEH) with regard to spinal level and to compare early and delayed onset cases. Summary of Background Data: PSEH is a serious complication of spinal surgeries. The difference in clinical manifestations between early and delayed PSEH remains unclear. Methods: Patients who underwent spinal surgeries between 1999 and 2013 at our institution, were reviewed through their medical records. For patients with PSEH, the incidence, duration to onset, duration from onset to evacuation, symptoms, recovery rate (American Spinal Injury Association grade), neurological outcomes, comorbidities, and preoperative use of anticoagulant drugs were examined. We next compared patients with early onset PSEH (onset until day 3) versus delayed onset (onset day 4 or later) regarding these clinical factors. Results: Fourteen patients (0.42%, 14/3371) developed symptomatic PSEH. Initial symptoms were observed between 0 and 7 days (mean 2.6 ± 2.4 d) and almost half (43%, 6/14) occurred during the delayed phase (mean 5.0 ± 1.1 d postsurgery). Paralysis was the predominant symptom in patients with cervical and thoracic surgeries (100%, 6/6), whereas severe pain was most frequent in patients with lumbar procedures (63%, 5/8) ( P  = 0.019). No significant differences were identified between early and delayed groups. Neurological outcome was good in 10 cases, partial in two cases, and poor in two cases. Conclusion: The frequency was consistent in every spinal region, and the symptoms due to PSEH were correlated with spinal level. Almost half the cases were diagnosed after a delay (day 4 or later), which supports the necessity to follow up patients with spinal surgeries more carefully for a week or so and to educate patients and comedical staff about the possibility of delayed hematoma disorders in order not to defer timely intervention. Level of Evidence: 4 Abstract : The overall incidence of symptomatic PSEH was 0.42%, which was consistent in every spinal region. The symptoms were correlated with spinal level, and almost half of the cases (43%) were diagnosed after a delay. Our results serve to raise the awareness of surgeons, patients, and comedical staff of delayed onset PSEH.